PREECLAMPSIA IN PREGNANT WOMEN: CLINICAL FEATURES AND ITS IMPACT ON PERINATAL OUTCOMES (Eurasian Journal of Medical and Natural Sciences, 2026)
Preeclampsia is one of the leading causes of maternal and perinatal morbidity and mortality. It is characterized by the development of arterial hypertension and proteinuria after the 20th week of pregnancy, and in severe cases may be accompanied by dysfunction of the liver, kidneys, and central nervous system. According to the World Health Organization, hypertensive disorders complicate 5–10% of all pregnancies.